Risk behavior score: a practical approach for assessing risk among men who have sex with men in Brazil - Rocha,Gustavo Machado (2018)
ABSTRACT HIV/AIDS epidemic is not well controlled, and multiple sexual behavior factors help explain high rates of HIV infection among men who have sex with men (MSM). This article proposes to exam the use of a potential risk behavior score for HIV infection, based on the type and number of sexual partners, and condom use, and their associated factors in a sample of MSM in Brazil. A cross sectional RDS (Respondent Driven Sampling) study was performed among 3738 MSM aged 18+ years old from ten Brazilian cities. The risk behavior score was composed by the number of male partners and anal condom use in the last year with steady, casual, and commercial partners. Most participants were 25+ years old (58.1%), non-white (83.1%), and single (84.9%). Final weighted ordinal logistic model showed that age ≤ 25 years old (p = 0.037), homosexual or bisexual identity (p < 0.001), sexual initiation before 15-year-old (p < 0.001), having sex with men only in the last 12 months (p < 0.001), frequent alcohol and illicit drug use (p < 0.001), and use of local sites to meet sexual partners in the last month were independently associated with higher scores of risky behavior. Specific strategies should be developed aimed at the MSM population. Additionally, pre-exposed prophylaxis (Prep) should be considered for those at higher score as a strategy for reducing risk for HIV infection in this population.